2014
DOI: 10.1039/c4tb00516c
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-3 antibody functionalized Prussian blue nanoparticles for targeted MR imaging and photothermal therapy of hepatocellular carcinoma

Abstract: MRI-guided photothermal therapy is becoming a more widely accepted minimally invasive technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 42 publications
5
67
0
Order By: Relevance
“…Although targeting can also be achieved using small molecules, peptides, aptamers and other biomolecules [15], we focus in this section on the use of antibodies. Surface modifications of nanoparticle systems ranging from metal particles to polymer and micellar structures allows covalent attachment of antibodies via methods such as amide bonds using EDAC NHS chemistry [16][17][18], dopamine-mediated bonding [19], maleimide groups [20], disulfide bonds [21] and the use of a hydrazide alkyl linker [22]. Regardless of the linkage, the formation of a protein corona surrounding the nanoparticle is likely to take place, thereby blocking recognition of the functional groups.…”
Section: Targeting Tumor Cells With Antibodiesmentioning
confidence: 99%
“…Although targeting can also be achieved using small molecules, peptides, aptamers and other biomolecules [15], we focus in this section on the use of antibodies. Surface modifications of nanoparticle systems ranging from metal particles to polymer and micellar structures allows covalent attachment of antibodies via methods such as amide bonds using EDAC NHS chemistry [16][17][18], dopamine-mediated bonding [19], maleimide groups [20], disulfide bonds [21] and the use of a hydrazide alkyl linker [22]. Regardless of the linkage, the formation of a protein corona surrounding the nanoparticle is likely to take place, thereby blocking recognition of the functional groups.…”
Section: Targeting Tumor Cells With Antibodiesmentioning
confidence: 99%
“…NPs can also be used to target the tumor stroma changing the tumor microenvironment from its pro-tumorigenic state to an antitumorigenic state. One study demonstrated the ability of nanoparticles to target the tumor endothelium and improve the anti-tumoral efficacy of paclitaxel, both in vivo and in vitro [27]. Another approach would be to target the macrophage because they are inherently phagocytic and may uptake nanoparticles either within the tumor or in the circulation and subsequently migrate towards to the tumor.…”
Section: Molecular Mechanism Of Nanoparticle-mediated Tumor Ablationmentioning
confidence: 99%
“…Imaging modalities, such as magnetic resonance imaging (MRI), ultrasound imaging, and X‐ray computed tomography (CT), are known as the most commonly used technologies in clinic to diagnose the tumor spatial location/size, track the drug's biodistribution, and monitor the therapeutic efficacy . In particular, MRI, which is based on nuclear magnetic resonance effect, offers multiple superiorities, such as high spatial and temporal resolution, unlimited tissue depth penetration, and exquisite soft‐tissue imaging with 3D anatomical details . However, conventional MRI alone cannot provide comprehensive diagnosis due to its inherent limitations, such as expensive costs, long scanning time, interference from image artifacts, and insensitivity to calcification, calculi, and bone cortex.…”
Section: Introductionmentioning
confidence: 99%